Transmission of the AC electric power to a long distance - Davydov G. I., Khoiutanov A. M., Vasilev P. F., Kobylin V. P., Samorodov G. I. (Interactive science, 2018)
there are two different ways to transmit the AC electric power for a long distance: a compensated, the half-wave and tuned to half-wave transmissions. The compensation of the wave length is an effective way to increase the distance and the capacity of the transmission line. Through the wave length compensation it might to give to a long distance line the properties of the short line (except the active power losses). But with the distance and capacity increasing also increases a capacity of the compensation devices. Therefore, usage of the half wave and tuned to a half wave transmission lines to transmit an AC electric power for a long distances is more effective because there is no need to additional expenses to reactive power compensation by the stability conditions. The boundary length of the tuning to a half-wave is defined in article. The advisability of the tuning to a half-wave is arises when the length of the line more than 1500 km. Otherwise it recommended to tune the line to a «zero length».
Keywords: пропускная способность; длинные линии электропередач; компенсирующие устройства; настройка на полуволну; long distances transmission lines; capacity; compensating devices; setting on a half-wave